2008
DOI: 10.1159/000146865
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Duck Enteritis Virus: Evolutionary Relationship in the Family <i>Herpesviridae</i>

Abstract: Objective: To understand the evolutionary relationship of duck enteritis virus (DEV) in the family Herpesviridae and the genome organization of DEV. Methods: A modified ‘targeted gene walking PCR’ method was used to amplify the unknown gene of DEV Clone-03 strain adjacent to a short stretch of known sequence. The assembled unknown fragment was confirmed to be a homologue of herpesviruses by BLAST analysis and comparison with other herpesviruses homologues. Open reading frames (ORFs) were determined and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…This phenomenon might be the result of an evolutionary event: the terminase-related UL15 coding sequence remained conserved for its importance in herpesvirus biology, while genes within the intron evolved via recombination and gene transfer between virus and vertebrate hosts since these events are common in herpesviruses [33]. In this interpretation, the fact that the pattern of ORF organization within the DEV UL15 intron is very similar to that of the corresponding regions of other alphaherpesviruses is another piece of direct evidence that DEV is a member of the subfamily Alphaherpesvirinae , which is in accordance with pervious findings [4,6,7,34]. …”
Section: Discussionsupporting
confidence: 74%
“…This phenomenon might be the result of an evolutionary event: the terminase-related UL15 coding sequence remained conserved for its importance in herpesvirus biology, while genes within the intron evolved via recombination and gene transfer between virus and vertebrate hosts since these events are common in herpesviruses [33]. In this interpretation, the fact that the pattern of ORF organization within the DEV UL15 intron is very similar to that of the corresponding regions of other alphaherpesviruses is another piece of direct evidence that DEV is a member of the subfamily Alphaherpesvirinae , which is in accordance with pervious findings [4,6,7,34]. …”
Section: Discussionsupporting
confidence: 74%
“…Genes in the UL region of DEV and their arrangement have been reported by our laboratory, and the results generally showed more similarity with Mardiviruses [8-13]. Another report showed that the LORF11 gene of the VAC strain is located at the leftmost end of the DEV genome, and that the LORF11 gene encoded a putative protein of 275 amino acids in the VAC strain [14]; both of these results differ from our previous results [12]. Meanwhile, several genes in the US region have also been reported [15-18]; however, the length of the putative proteins encoded by the US10 gene and US7 gene has been debated.…”
Section: Introductioncontrasting
confidence: 83%
“…The genome structure and the gene layout of this fragment are depicted in Figure 1. The fragment contained part of the sequence of the LORF11 gene [12], the rightmost part of the L region, the US region and its flanking sequences, and inverted repeats of the short region (IRS and TRS). The L region and IRS were interrupted by a set of tandem repeat sequences designated as α-type-like sequences [13], as in the case of the two regions in herpes simplex virus (HSV) [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations